Rats’ performance in a suboptimal choice procedure implemented in a natural-foraging analogue - Fernanda González-Barriga; Vladimir Orduña (Animal Cognition)
Abstract Rats and pigeons have shown striking differences in their behavior in the suboptimal choice procedure: while pigeons show a strong and consistent preference for the discriminative alternative, most studies performed with rats have found optimal preferences, and in the cases in which suboptimal preferences have been reported, those results have not been replicated. Currently, there is no consensus about the reasons for these discrepant results between species, but different explanations have been proposed either with an empirical base or exclusively in theoretical terms. In the latter category it has been proposed that the discrepancy might have arisen because of differences in the relationship between the natural foraging response of each species, and the response required in the laboratory. For analyzing this possibility, we conducted two experiments carried out within a maze that was specifically designed to allow rats to display behaviors related to their natural foraging. In experiment 1, we explored rats’ preferences when facing a discriminative alternative with probability of reinforcement (p) = 0.5, and a non-discriminative alternative with p = .75. In experiment 2, we evaluated preferences when the discriminative alternative had p = .20 and the non-discriminative had p = .50, rats were evaluated in a closed economy, with longer terminal links, and were allowed to escape from the outcome found. In both studies, rats showed a strong preference for the non-discriminative alternative and showed very high levels of discrimination between the positive and the negative outcomes of the discriminative alternative.